The Impact of Financial Constraint on Cash Holdings Behaviour and the Value of Cash Holdings and Investment: Evidence from Chinese Listed Firms - Xie, Zheyang (2019)
Cash and cash equivalent are the significant item for enterprises which can satisfy the enterprise operation and investment demand. Holding cash can create profit for companies which is a way to reflect the firms’ value. Moreover, firms’ cash holdings are strongly impacted by financial constraint. In this dissertation, four main popular proxies are used to detect financial constraint which are firm size, annual payout ratio, debt ratio and whether owned by the government. Notably, based on the result of all regression, the annual payout ratio is not an appropriate indicator of financial constraint for Chinese listed companies. The sample is all Chinese companies listed of A-share from 2009 to 2018, and the fixed random model is selected in all regression in this paper. According to the report, the constrained firms are more likely to hold more cash from cash flow. Besides, for the financially constrained companies, the marginal value of holding cash and investment is profitable than the unconstrained firms.